Memories of Hiroshima - Abd Razak, Dzulkifli (2011)
WHEN I was young, my father used to narrate the bombing of Hiroshima, Japan in 1945 and the devastation it caused both to human lives and the physical environment. This is one event that he will not be able to forget because of its tremendous impact on his teenaged life. Somehow he wants the experience to rub off on his family as much as possible, given the numerous lessons therein even until today.